THE ASSESSMENT OF MOCHI QUALITY WAS FORTIFIED SNAKEHEAD FISH (Channa striata) PROTEIN CONCENTRATE - Andriaryanto '; Dewita '; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractMochi is a Japanese traditional foods are quite popular in Indonesia. This product is madefrom glutinous rice flour and generally spherical and semi wet. To improve the proteincontent of mochi, the research about snakehead fish (Channa striata) protein concentrate wasdone. The research was conducted on July 2014 on Fisheries Processing Technology andFisheries Chemical Laboratory Faculty of Fisheries and Marine Science. This study wasaimed to determine the best fish protein concentrated to mochi quality. The methode used inthis research was experimental methode; mochi was fortified with different fish proteinconcentrate (0%, 3.5%, and 4.5%) by using a Completely Randomined Design. The resultsshowed that the mochi with addition 4.5% of fish protein concentrate was the best treatmentwith organoleptic quality characteristics of taste 8.17; texture 8.27; appearance 8.01; and odor8.13. Proximate analysis for water content 37.62%; ash content 0.98%; and protein content23.61%.Keywords: Quality, Mochi, Fortified, Fish Protein Concentrate, Channa striata